Web Solution Based on QR Code for the Traceability of the Wood Transformation Process - Amaya, Edgar Diaz (2022)
The information's management on the traceability of wood in Peru is complicated by multiple causes. In this article we present our project, which seeks to propose a technological model that allows greater efficiency in the management of timber information so that sawmills in Peru can improve their administration. Our proposed model allows us to appreciate a possible improvement in the time it takes to obtain information on the traceability of wood compared to the traditional way in which work continues in Peru. Also, in the investigation a prototype application of traceable information was developed. The main contribution of the research consists in the design of a technological model that serves as a reference to develop a technological solution for the traceability of wood in Peru.